An innovative mixotrophic approach of distillery spent wash with sewage wastewater for biodegradation and bioelectricity generation using microbial fuel cell. (June 2018) - Nayak, Jagdeep K.; Amit; Ghosh, Uttam K.
Abstract: In the present study, H-type microbial fuel cell (H-MFC) has been used to treat distillery spent wash (DSW) diluted with sewage wastewater (SWW) at different mixing ratio. Mixture of DSW and SWW was used as substrate in anaerobic environment. The cathodic compartment was filled with BBM media and microalgae ( Scenedesmus abundans) . CO2 generated during breakdown of organic substrates by anaerobes present in DSW was utilized by microalga Scenedesmus abundans for photosynthesis. A consortium of two bacteria ( Pseudomonas aeruginosa and Bacillus cereus ) was used for the 21 days period of DSW treatment. Significant reduction in chemical oxygen demand (COD) in the order of 66% to 78.66% was observed. At 50:50 ratio of DSW and SWW, total dissolved solid (TDS) of 39.66% and total suspended solid (TSS) of 97% were removed. A maximum power density (PD) of 836.81 mW/m 2 and open circuit voltage (OCV) of 745.13 mV were obtained along with biomass yield of 0.74 g/L d −1 with above ratio of DSW and SWW. This study demonstrated that proper dilution of Distillery spent wash with sewage wastewater may leads to an efficient wastewater remediation and energy production.